The comparative effects of two methods of teaching division of whole numbers in grade two - Aliping, Susana Cayagan
The study seeks to determine the better teaching approach in teaching division of whole numbers to Grade four pupils at Roxas Elementary School in Baguio. The two teaching approaches considered are the two division algorithms -- the subtractive algorithm and the standard algorithm.